Gavilán, Mirta (comp.) 2012. Equity and occupational educative guidance : Buenos Aires: Lugar Editorial - Orientación y Sociedad (2012)
This book presents the outputs undertaken by the research staff that is composed by the Chairs of Vocational Guidance and Preventive Psychology, from the Faculty of Psychology of the National University of La Plata. The works included correspond to the two last completed projects: 1) Vocational and Occupational Guidance in populations of high psycho-social vulnerability. 2) Assessment strategies of Vocational and Occupational Guidance aimed at reversing psycho-social inequity, They are both funded by the Secretariat of Science and Technique and the University Policies Secretariat, through the incentive Program for researcher professors.